Behavior of Russian Premium Fashion Consumers and Designers after the COVID-19 Pandemic and International Sanctions - Irina I. Skorobogatykh; Irina P. Shirochenskaya; Galina S. Timokhina; Taira V. Murtuzalieva; Sergey V. Mkhitaryan (Emerging Science Journal, 2023)
The purpose of this paper was to investigate the emerging changes in Russian premium fashion brand consumers' behavior on the eve of the COVID-19 pandemic and international economic sanctions, the impact on foreign fashion brands' decisions to leave the market, and the willingness of some Russian fashion designers to scale their businesses and occupy vacated market niches. This problem had arisen for the first time; the situation is unexpected and unique. Therefore, the researchers combined multiple methods of data collection: (1) Observation; (2) Netnography to identify emerging changes in Russian consumers' behavior, which increases the objectivity of the data obtained since personal contact was excluded; and (3) Expert in-depth interviews to assess the situation by Russian fashion designers. QDA and qualitative content analysis were used. Fashion designers in Russia percept the situation as an opportunity for business development, similar to the situation that occurred in Iran, but entrepreneurs understand the market risks and expect more serious measures of state support for business. The results may inform state policymakers and stakeholders about the stated changes in consumer behavior and the capabilities of Russian entrepreneurs to scale the business, which will help identify possible growth vectors for domestic fashion designers in the premium sector. Doi: 10.28991/ESJ-2023-SPER-010 Full Text: PDF